Administracyjnoprawne uwarunkowania działalności agroturystycznej. Studium prawnoporównawcze - Kapała, Anna (Wydawnictwo Naukowe UAM, 2009)
Polish legislation lacks the legal notion of agro-tourism. Neither, there is any legal act dealing with the issue in a complex way. Whereas in Italian law, agro-tourism activity is regulated by a separate act with all legal-administrative conditions contained therein. The aim of these considerations is to draw a relatively exhaustive outline of legal administrative conditions for exercising agro-tourism activity under Polish law. To meet this purpose an inquiry into various legal acts dealing with the issue is required. The author concludes by claiming that although it is possible to point at legal administrative conditions for agro-tourism activity with some of them being of similar - to Italian - detailed scope, but there exists no complex regulation, specifically designed for agrotourism activity. Therefore, the author finds it necessary and most appropriate to consolidate all provisions dealing with this form of tourism into one single act.

Nella legislazione polacca non esiste una nozione giuridica di agriturismo. Manca altresi un atto giuridico che regoli tutti gli aspetti dell’esercizio dell’attivitá agrituristica. Invece, nel diritto italiano, all'agriturismo é dedicata una legge che disciplina ogni aspetto dell’attivitá agrituristica, anche quello amministrativo. Lo scopo della trattazione é tentare di individuare, in modo possibilmente esaustivo e sistemático, la disciplina amministrativa dell’attivitá agrituristica in Polonia. Per fare ció si rende opportuno ricorrere alie norme concementi Pagriturismo contenute in diversi atti giuridici. In conclusione l’autrice afferma, tra l’altro, che é possibile individuare, anche nella legislazione polacca, le norme che disciplinano i presupposti amministrativi all’esercizio dell’attivitá agrituristica in un modo pieno ed esaustivo, pur mancando delle specifiche norme adottate in tal senso. Appare pertanto necessario uniré e sistemare in un único atto dedicato all’agriturismo tutte le norme riguardanti l’esercizio di tale forma di turismo.
Legal-administrative conditions for tourism activities in agriculture. Comparative study
La disciplina amministrativa dell'attivitá agrituristica. Profili comparati